Multidimensional features of pain in patients with chronic neck pain - Fabianna Resende de Jesus-Moraleida; Leani Souza Máximo Pereira; Cristiane de Melo Vasconcelos; Paulo Henrique Ferreira
Abstract Introduction: Chronic neck pain is associated with significant health costs and loss of productivity at work. Objective: to assess pain and disability in individuals with chronic neck pain. Methods: 31 volunteers with chronic neck pain, mean age 29, 65 years, were assessed using the McGill Pain Questionnaire in Brazilian version (Br-MPQ) and Neck Disability Index (NDI). The Br-MPQ analysis was performed based on the numerical values associated with the words selected to describe the experience of pain (Pain Rating Index - PRI), and present pain intensity (PPI). NDI was used to evaluate the influence of neck pain in performance of everyday tasks. Finally, we investigated the association between PPI and NDI. Results: PRI revealed that the most significant dimension was the sensory pain (70%), and the number of chosen words was 10 (2,62) out of 20 words. Mean PPI value was 1,23 (0,76) in five points; 40% of participants described pain intensity as moderate. NDI score was 9,77 (3,34), indicating mild disability. There was a positive association between disability and pain intensity (r = 0,36; p =0,046). Pain intensity and duration of pain were not associated. Conclusions: Findings of this study identified important information related to neck pain experienced by patients when suffering from chronic neck pain, moreover, the association between disability and pain intensity reinforces the importance of complementary investigation of these aspects to optimize function in them.